PREVENTION OF Β THALASSEMIA IN NORTHERN ISRAEL - A COST-BENEFIT ANALYSIS. - Ariel Koren; Lora Profeta; Luci Zalman; Haya Palmor; Carina Levin; Ronit Bril Zamir; Stavit Shalev; Orna Blondheim (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Background:β Thalassemia major is characterized by hemolytic anemia, ineffectiveerythropoiesis and hemosiderosis. About 4 % of the world population carries a Thalassemiagene. Management includes blood transfusions and iron chelation, this treatmentis costly and population screening may be significantly more cost benefit. Purpose: Thepurpose of the current study is to analyze the cost of running a preventionprogram for β Thalassemia in Israel and compare it to the actual expensesincurred by treating Thalassemia patients. Methods: Threecost parameters were analyzed and compared: The prevention program, routinetreatment of patients and treatment of complications. An estimation of theexpenses needed to treat patients that present with complications werecalculated based on our ongoing experience in treatment of deterioratingpatients. Results andConclusions: The cost of preventing one affected newborn was $63,660 comparedto $1,971,380 for treatment of a patient during 50 years (mean annual cost:  $39,427). Thus, the prevention of 45 affectednewborns over a ten years period represents a net saving of $88.5 million tothe health budget. Even after deducting the cost of the prevention program ($413.795/yr.), the program still represents abenefit of $ 76 million over ten years. Each prevented case could pay thescreening and prevention program for 4.6 ys.